2016
DOI: 10.7324/japs.2016.60310
|View full text |Cite
|
Sign up to set email alerts
|

Radiomodulatory Role of Psidium guajava Leaf Extracts against X-ray Induced Genotoxicity, Oxidative stress and Apoptosis in albino Wistar Rat Model

Abstract: In the present study we investigated the radioprotective activity of hydroalcoholic leaf extracts of Psidium guajava (P.G) against rats exposed to X rays. Exposure to ionizing radiation like X rays induces oxidative damage in normal tissues leading to their death or transforming them into cancerous tissues. To study the optimum dose of radioprotection, rats were administered with different doses (50,100,200,400 mg/kg body weight) of Psidium guajava leaf extracts daily for five consecutive days. One hour after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…An increase in MDA levels shows the development of oxidative stress by ionizing radiations. This observation is in agreement with the study of Kumar et al [17].…”
Section: Liversupporting
confidence: 94%
“…An increase in MDA levels shows the development of oxidative stress by ionizing radiations. This observation is in agreement with the study of Kumar et al [17].…”
Section: Liversupporting
confidence: 94%
“…Previous studies showed TUNEL‐positive cells or bodies in irradiated animals (Jiang et al., ; Kim et al., ). There are reports of decrease in apoptosis induced in X‐ray‐exposed animals which were treated with various plant extracts like Psidium guajava , Panax ginseng , Punica Granatum (Kim et al, ; Kumar et al., ; Toklu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the leaves can act as radio modulators for cancer patients because by preventing DNA damage and apoptosis. [ 140 ], as well as protective agents by restoring the normal values of sperm viability, sperm count, sperm motility, and sperm-head abnormality caused by caffeine-induced spermatotoxicity [ 141 ].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%